Nomogram Models to Predict Postoperative Hyperlactatemia in Patients Undergoing Elective Cardiac Surgery - Wang, Dashuai; Wang, Su; Wu, Jia; Le, Sheng; Xie, Fei; Li, Ximei; Wang, Hongfei; Huang, Xiaofan; Du, Xinling; Zhang, Anchen (Frontiers in Medicine, 2021)
Objectives: Postoperative hyperlactatemia (POHL) is common in patients undergoing cardiac surgery and is associated with poor outcomes. The purpose of this study was to develop and validate two predictive models for POHL in patients undergoing elective cardiac surgery (ECS). Methods: We conducted a multicenter retrospective study enrolling 13,454 adult patients who underwent ECS. All patients involved for analysis were randomly assigned to a training set and a validation set. Univariate and multivariate analysis were performed to identify risk factors for POHL in the training cohort. Based on those independent predictors, the nomograms were constructed to predict the probability of POHL and were validated in the validation cohort. Results: A total of 1,430 patients (10.6%) developed POHL after ECS. Age, preoperative left ventricular ejection fraction, renal insufficiency, cardiac surgery history, intraoperative red blood cell transfusion, and cardiopulmonary bypass time were independent predictors and were used to construct a full nomogram. The second nomogram was constructed comprising only the preoperative factors. Both models showed good predictive ability, calibration, and clinical utility. According to the predicted probabilities, four risk groups were defined as very low risk (<0.05), low risk (0.05-0.1), medium risk (0.1-0.3) and high risk groups (>0.3), corresponding to scores of ≤180 points, 181-202 points, 203-239 points and >239 points on the full nomogram. Conclusions: We developed and validated two nomogram models to predict POHL in patients undergoing ECS. The nomograms may have clinical utility in risk estimation, risk stratification, and targeted interventions.